The Cooling Effect of Plant Configuration on Urban Parks Green Space in Temperate Continental Climate Zones - Nie, Xiaomeng; Lin, Juntian; Ma, Juanli; Cao, Bing; Li, Yinghong; Lu, Yu; Bian, Yingying; Liu, Jiajia; Zhang, Ping (Applied spatial analysis and policy, 2024)
In temperate continental climate zones with hot summers and significant diurnal temperature differences, the park green space construction is an effective way to increase park visitor comfort and mitigate urban daytime high temperatures. In this experiment, 42 plant configurationss were selected and classified into 12 configuration typesbased on three indicators of the underlying surface, tree species, and canopy density in 6 parks in Yinchuan, Wuzhong and Zhongwei cities of Ningxia, China, in the summer of 2019 and 2020.The air temperature of the sample plots (8:00 ~ 18:00) was measured with a Kestrel NK5500 weather station, and the daily air temperature variation pattern of each typical plant configuration was analyzed, the cooling effect of the 12 configuration types and its controlling factors were revealed based on the air temperature difference (park air temperature—weather station air temperature). There was a significant negative correlation between canopy density and the cooling effect of green lands( P < 0.05,the same below), but the underlying surface and tree species configuration of the green lands could not contributed to the cooling effect. The park green lands with ≥ 40% canopy density had a significant cooling effect compared with hard-paved park areas during the daytime (8:00–18:00). The average daytime temperature of green areas with 40–60% canopy density decreased by about 0.5 °C, and those with > 60% canopy density decreased by 1.1–1.5 °C. In the daytime, the cooling effect of green areas was stable from 8:00 to 12:00 and from 12:00 to 15:00, when the degree of canopy density reached 50% and 40% and above, respectively. And from 15:00 to 18:00, all plant configurations (including grass) had a cooling effect, and the overall cooling effect increased with the process of canopy density.This study provides guidance for the risk management of summer high temperatures and the planning of public green space construction based on cooling effects in cities of continental climate zones.